INFLUENCE STUDENT’S LEARNING MOTIVATION AND ATTITUDE ON THE SUBJECTS OF CIVICS - Kartika Sari S; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2012)
This study aimed to analyze the effect of motivation on learning readiness class XI IPS in SMA N 1 Bandar Lampung school year 2012/2013 and the influence on student attitudes toward the subject Civics class XI student readiness IPS in SMA Negeri 1 Bandar Lampung of the school year 2012/2013. This study uses descriptive correlational research subject is social studies class XI students totaling 115 students. Samples were taken for this study was 25% or 29 students. Data collection using questionnaire techniques, interview and observation. Data analysis using Chi square formula. The results 1. There is the influence of motivation toward learning readiness class XI IPS in Bandar Lampung SMA Negeri 1 and 2 2012/2013 school year. There is influence between attitudes of students in Civics subject to the readiness of IPS XI grade student at SMA Negeri 1 Bandar Lampung 2012/2013 school year. Keywords: Motivation, Learning, Attitudes, Learning Readiness, Students.